How are Media’s Reports on China’s Products? A Content Analysis on Indonesian Online Media concerning Sinovac Vaccine - Ali, Rokhman (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The Covid-19 pandemic currently hits the world, and no country is not affected by the pandemic, included Indonesia. Every country issued policies to stop the pandemic and mitigate its impacts. Besides economy-related policies, the governments in many countries also issued policies in the health sector, including vaccination policy. The Republic of Indonesia Government also issued a policy in public health that is the National Vaccination Policy. The vaccine mainly used was Sinovac, made in China. This research attempted to analyze how the Indonesian online media reported Sinovac. The most representative online media had been chosen as the primary target. The method used was content analysis on the news published in the target media within seven months from January to July 2021. This research concluded two propositions. First, the more sensitive a product will receive, the more public responses from various interest groups. Second, if a product is ineffective and has weaknesses, the media will investigate and report more frequently.